Hydrothermal Synthesis and Characterization of Mn-Doped VO2 Nanowires. (24th January 2019) - Long, G.; Matatov, David; Suissa, Acher; Feddi, Elmustapha; Yadri, M. EL; Feddi, Kawtar; Sadoqi, M.
Abstract: Monoclinic VO2 is a known polymorph of vanadium dioxide that has received much attention due to its oxidative capabilities, geometric configuration, and promising applications in functional windows. VO2 can usually be obtained through a hydrothermal method under high pressure. In this work we report a synthesis of VO2 doped with Manganese using a rapid single-step hydrothermal process with V2 O5, manganese (II) acetate and citric acid as precursors. Different syntheses were carried out in which the concentration of V2 O5 and citric acid remained constant whereas the concentration of manganese (II) acetate was varied. The reactants underwent a stirring phase for 30 minutes before being loaded into a hydrothermal reactor for 2.5 hours at 200°C. The resultant was washed three times to remove the residual precursors. Imaging and spectroscopy characterizations such as TEM, SEM and UV-VIS-NIR have been performed on different doping concentration and the results display a dependence on doping concentrations.